Balancing omega-6 and omega-3 fatty acids in ready-to-use therapeutic foods (RUTF) - Brenna, J; Akomo, P; Bahwere, P; Berkley, J; Calder, P; Jones, K; Liu, L; Manary, M; Trehan, I; Briend, A (BioMed Central, 2015)
Ready-to-use therapeutic foods (RUTFs) are a key component of a life-saving treatment for young children who present with uncomplicated severe acute malnutrition in resource limited settings. Increasing recognition of the role of balanced dietary omega-6 and omega-3 polyunsaturated fatty acids (PUFA) in neurocognitive and immune development led two independent groups to evaluate RUTFs. Jones et al. (BMC Med 13:93, 2015), in a study in BMC Medicine, and Hsieh et al. (J Pediatr Gastroenterol Nutr 2015), in a study in the Journal of Pediatric Gastroenterology and Nutrition, reformulated RUTFs with altered PUFA content and looked at the effects on circulating omega-3 docosahexaenoic acid (DHA) status as a measure of overall omega-3 status. Supplemental oral administration of omega-3 DHA or reduction of RUTF omega-6 linoleic acid using high oleic peanuts improved DHA status, whereas increasing omega-3 alpha-linolenic acid in RUTF did not. The results of these two small studies are consistent with well-established effects in animal studies and highlight the need for basic and operational research to improve fat composition in support of omega-3-specific development in young children as RUTF use expands.